Activities and Education in Logistics - Pašagić Škrinjar, Jasmina; Ivaković, Čedomir; Šimunović, Ljupko (Promet - Traffic&Transportation, 2008)
Logistic approach to traffic means new business policy,economy and ownership, new internal organization, externaland internal communication, different corporate cultures, humanresources management using scientific methods, trainingand education, changed management type and awarding system,knowledge of information technology, communicationskills, electronic commerce, etc. Education is part of all theseelements. The introduction of logistics in all the business activitieshas been imposed due to the following reasons: because ofthe life-cycle shortening of the product and its delivery, becauseof sudden technological development, because of productionand market globalization, because of the increase in competitiveness.This paper describes first various logistic activities with theindication of practical and scientific approaches. The logisticsapproach in the traffic activities requires upgrading of the professionaland scientific level to a higher one which means additionaltraining and acquiring of new skills as well as new technologiesfor the employees.The basic aim of research was to specifY the basic logisticsactivities and problems in order to indicate the need of differentforms of education. Fast technological and social changes requireconstant improvement and modification of professionalknowledge and acqui1ing of new scientific methods and skills.